Charge transport in lightly reduced graphene oxide : a transport energy perspective - Kajen, R. S. (2013)
Significant variation in the charge transport behaviour in graphene oxide (GO) ranging from Schottky to Poole-Frenkel and to space charge limited transport exists. These have been extensively reported in the literature. However, the validity of such conventional charge transport models meant for delocalized carriers, to study charge transport through localised states in GO, a disordered semiconductor is open to question. In this work, we use the concept of transport energy (TE) to model charge transport in lightly reduced GO (RGO) and demonstrate that the TE calculations match well with temperature dependent experimental I-V data on RGO. We report on a temperature dependent TE ranging from a few 10meV to 0.1 eV in slightly reduced GO. Last, we point out that, despite the success of several delocalised charge transport models in estimating barrier heights that resemble the TE level, they remain largely accidental and lack the insight in which the TE concept provides in understanding charge transport in RGO.